Using hospitalization rates to track the economic costs and benefits of improved diabetes care in the Americas : A proposal for health policy makers - Gagliardino, Juan José (2000)
Diabetes presents a particular challenge to developing countries for many reasons. First, the incidence and prevalence of diabetes are increasing dramatically in devel oping countries with westernization (18); the World Health Organization (WHO) estimates that developing nations will have the largest prevalence of the disease in the near future (19). Second, 80% of the diabetes disability-adjusted life-years lost worldwide already occurs in developing countries (20). Third, despite increasing knowledge of and technologies for the control and treatment of diabetes and its complications, the cost of new technologies have made them inaccessible in developing countries. Lastly, many countries face serious constraints in their health budgets; allocation or reallocation of funds will require careful prioritization to resolve the critical problems that diabetes increasingly presents. Unfortunately, health policy makers are frequently unaware of (or have failed to act upon) either the strong evidence for the role of lifestyle changes (e.g., adopting healthy lifestyle habits, increasing physical activity, and adhering to an appropriate diet [21,22]) in the primary prevention of type 2 diabetes or the therapeutic and educational strategies to prevent or delay diabetes complications.